Translation, humour and literature - Chiaro, Delia, 1953- (Translation and humour, 2010)
Translation studies and humour studies are disciplines that have been long-established but seldom looked at in conjunction. This volume uses literature as the common ground and examines issues of translating humour within a range of different literary traditions. It begins with an analysis of humour and translation in every day life, including jokes and cross-cultural humour, and then moves on to looking at humour and translation in literature through the ages. . Despite growing interest and a history of collaborative study, there has been little translation studies scholarship published in.